Gospodarka na dopingu, czyli jak wywołać kryzys finansowy gospodarki - Kalinowska, Katarzyna (Gospodarka w Praktyce i Teorii, 2012)
The aim of this paper is empirical analysis of the Austrian theory which points that a monetary shock disturbs relative prices, such as the term structure of interest rates and leads to economic breakdown. Empirical evidence on Austrian Business Cycle is based on some economic crisises from 19th, 20th and 21st century. The paper also points out other than central bank`s monetary policy factors which affect the level of market interest rates.